Colon ischemia in patients with severe COVID-19: a single-center retrospective cohort study of 20 patients : short communication - Yang, Cui; Hakenberg, Priska; Weiß, Christel; Herrle, Florian; Rahbari, Nuh Nabi; Reißfelder, Christoph; Hardt, Julia (International journal of colorectal disease, 2021)
Thromboembolic complications due to COVID-19 are common in patients requiring critical care and are associated with high morbidity and mortality rates. The aim of this study was to evaluate clinical manifestations and postoperative outcomes after colectomy for COVID-19-associated colonic ischemia in the first versus the second wave of the pandemic.